Зона заражения-2: [роман] / Александр Афанасьев - Афанасьев Александр (Враг у ворот, 2016)
Экземпляры: ф.5 (20171004) / Инвентарный номер: 49293 / Цена: 255.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 94 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4